Equipment noise and worker exposure in the coal mining industry - Bauer, Eric R. (Information circular (National Institute for Occupational Safety and Health), 2006)
"Prolonged exposure to loud noise can cause permanent damage to the auditory nerve and/or its sensory components. Despite regulations and efforts by government and industry to reduce noise-induced hearing loss (NIHL), it is still a problem in the U.S. coal mining industry. The Mine Safety and Health Administration noise standard (30 CFR3 62), which was enacted in September 2000, is aimed at reducing NIHL in the mining industry. To address NIHL in various aspects of coal mining and provide the necessary information to effectively implement control technologies, the National Institute for Occupational Safety and Health conducted a cross-sectional survey of noise sources and worker noise exposures. Noise surveys consisting of full-shift worker noise exposure (dose) determination, timemotion studies (task observations), and equipment and/or area noise profiling were completed in 8 underground coal mines, 10 surface coal mines, and 8 coal preparation plants. The studies revealed that more than 40% of all workers monitored were subject to noise exposures above 90 dBA TWA8. A summary of these studies is presented, their application to administrative and engineering controls is discussed, and exposure reduction methods are reviewed."--Page [1].